2018
DOI: 10.1097/naq.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Dissemination of a Department of Veterans Affairs Oral Care Initiative to Prevent Hospital-Acquired Pneumonia Among Nonventilated Patients

Abstract: Implementation and dissemination of an oral care initiative enhanced the safety and well-being of Veterans at the Salem VA Medical Center by reducing the risk of non-ventilator-associated hospital-acquired pneumonia (NV-HAP). The incidence rate of non-ventilator-associated hospital-acquired pneumonia decreased from 105 cases to 8.3 cases per 1000 patient-days (by 92%) in the initial VA pilot, yielding an estimated cost avoidance of $2.84 million and 13 lives saved in 19 months postimplementation. The team was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
0
24
1
Order By: Relevance
“…A few recent studies have reported that the use of oral care prevented ND pneumonia in high-risk patients (eg, neurologic injury patients, older adults). [35][36][37] Although we did not detect an association between chlorhexidine mouthwash and ND pneumonia rates, this discrepancy could be due to targeted use of oral care with chlorhexidine at UNC Hospitals. In contrast to its universal use in prior studies, only 8% of hospitalized patients included in this analysis received this treatment.…”
Section: Discussioncontrasting
confidence: 62%
“…A few recent studies have reported that the use of oral care prevented ND pneumonia in high-risk patients (eg, neurologic injury patients, older adults). [35][36][37] Although we did not detect an association between chlorhexidine mouthwash and ND pneumonia rates, this discrepancy could be due to targeted use of oral care with chlorhexidine at UNC Hospitals. In contrast to its universal use in prior studies, only 8% of hospitalized patients included in this analysis received this treatment.…”
Section: Discussioncontrasting
confidence: 62%
“…21,22 Efforts at reduction in NV-HAP incidence have been challenged by limitations in improving the quality and frequency of oral care, often considered to be fundamental care. 8,9,13 Therefore, a critical lesson learned was the need to shift nursing beliefs regarding oral care from solely a comfort measure to an essential infection control practice, which can be tracked and counted as a direct accountability measure for nursing services. As the team began to discuss oral care as a critical and expected standard of care (using handwashing as an analogy), it became less likely to be viewed as optional care.…”
Section: Discussionmentioning
confidence: 99%
“…As of the end of fiscal year 2020, DoE estimates that eight National Diffusion Practices have been implemented at numerous facilities across the VHA and impacted an estimated 570 000 veterans in fiscal years 2019 and 2020. Example DoE Promising Practices include (a) enhancing oral hygiene of inpatients with the goal of preventing non‐venerator associated pneumonia 18,19 ; (b) encouraging the early ambulation of hospitalized patients with the goal of preventing functional decline 20‐22 ; and (c) use of automated review of electronic health record data to identify prescriptions that are potential candidates for discontinuation 23…”
Section: Context‐diffusion Of Excellence Programmentioning
confidence: 99%
“…We end with a set of lessons to consider when conducting embedded projects. non-venerator associated pneumonia 18,19 ; (b) encouraging the early ambulation of hospitalized patients with the goal of preventing functional decline [20][21][22] ; and (c) use of automated review of electronic health record data to identify prescriptions that are potential candidates for discontinuation. 23…”
Section: Introductionmentioning
confidence: 99%